Map-based cloning of the Hessian fly resistance gene H13 in wheat - Joshi, Anupama (Kansas State University, 2018)
H13, a dominant resistance gene transferred from Aegilops tauschii into wheat (Triticum aestivum), confers a high level of antibiosis against a wide range of Hessian fly (HF, Mayetiola destructor) biotypes. Previously, H13 was mapped to the distal arm of chromosome 6DS, where it is flanked by markers Xcfd132 and Xgdm36. A mapping population of 1,368 F2 individuals derived from the cross: PI372129 (h13h13) / PI562619 (Molly, H13H13) was genotyped and H13 was flanked by Xcfd132 at 0.4cM and by Xgdm36 at 1.8cM. Screening of BAC-based physical maps of chromosome 6D of Chinese Spring wheat and Ae. tauschii coupled with high resolution genetic and Radiation Hybrid mapping identified nine candidate genes co-segregating with H13. Candidate gene validation was done on an EMS-mutagenized TILLING population of 2,296 M₃ lines in Molly. Twenty seeds per line were screened for susceptibility to the H13-virulent HF GP biotype. Sequencing of candidate genes from twenty-eight independent susceptible mutants identified three nonsense, and 24 missense mutants for CNL-1 whereas only silent and intronic mutations were found in other candidate genes. 5’ and 3’ RACE was performed to identify gene structure and CDS of CNL-1 from Molly (H13H13) and Newton (h13h13). Increased transcript levels were observed for H13 gene during incompatible interactions at larval feeding stages of GP biotype. The predicted coding sequence of H13 gene is 3,192 bp consisting of two exons with 618 bp 5’UTR and 2,260 bp 3’UTR. It translates into a protein of 1063 amino acids with an N-terminal Coiled-Coil (CC), a central Nucleotide-Binding adapter shared by APAF-1, plant R and CED-4 (NB-ARC) and a C-terminal Leucine-Rich Repeat (LRR) domain. Conserved domain analysis revealed shared domains in Molly and Newton, except for differences in sequence, organization and number of LRR repeat in Newton. Also, the presence of a transposable element towards the C terminal of h13 was indicative of interallelic recombination, recent tandem duplications and gene conversions in the CNL rich region near H13 locus. Comparative analysis of candidate genes in the H13 region indicated that gene duplications in CNL encoding genes during divergence of wheat and barley led to clustering and diversity. This diversity among CNL genes may have a role in defining differences in the recognition specificities of NB-LRR encoding genes. Allele mining for the H13 gene in the core collection of Ae. tauschii and hexaploid wheat cultivars identified different functional haplotypes. Screening of these haplotypes using different HF biotypes would help in the identification of the new sources of resistance to control evolving biotypes of HF. Cloning of H13 will provide perfect markers to breeders for HF resistance breeding programs. It will also provide an opportunity to study R-Avr interactions in the hitherto unexplored field of insect-host interaction.
Keywords: Wheat; Hessian fly; Plant insect interactions; R gene; CC-NB-LRR protein; Gall midge; H13; Haplotype